Can electric vehicles be an alternative for traditional fossil-fuel cars with the help of renewable energy sources towards energy sustainability achievement? - Al-Ghaili A.M. (Springer Nature, 2023)
Climate change; Electric vehicles; Energy efficiency; Fossil fuels; Sustainable development; Charging station; Electric vehicle charging; Energy sustainability; Fuel vehicles; Renewable energies; Renewable energy source; Renewables; Sustainable energy; Transportation industry; Vehicle technology; Renewable energy resources